ANALISIS FAKTOR PEMILIHAN MEDIA SOSIAL LINE DI KALANGAN REMAJA KOTA BANDUNG - Nofia Nandha Rani; Dini Salmiyah Fithrah Ali (Fakultas Dakwah dan Komunikasi, 2019)
The increasing of internet usage triggered the growth of social media activity. One of the social media which rose significantly is Line. Three years after Line debut, statistic showed that Line has 470 million users and the application has been downloaded over 1 million times in all over the world.This research is to determine what factors that influence people in Bandung City in deciding to choose social media Line. The theory that used in this research isStimulus Organism Respons Theory.. This research is using a descriptive method to visualize systematically, factually and accuracy regarding facts, characters and relation with the phenomena to be explored. Done by a survey to 180 people of Bandung City which have been chosen through multi-usage cluster sampling technique. Data that has been gathered then handle with using analysis factor method on SPSS 20.This research resulted in three factors which became the factor in choosing social media Line in Bandung area that has been obtained through analysis factor process. Those three factors in sequence are Networking Interactions factor consist of interaction and networking, User Information factor, including information, Social Simulation, User content and Archive factor. The rest another factor that owned by the user in choosing social media Line in Bandung area.